Analysis of characteristics of four patients with adrenal unicentric Castleman disease - Yu, Hao; Wang, Yuepeng; Li, Yijun; Du, Jin; Guo, Qinghua; Gu, Weijun; Lyu, Zhaohui; Dou, Jingtao; Mu, Yiming; Zang, Li (Frontiers in Endocrinology, 2023)
Background: Castleman Disease (CD) is a group of diseases with characteristic lymph node histopathology, characterized by marked enlargement of deep or superficial lymph nodes. Adrenal CD is rarely reported, and an accurate preoperative diagnosis of adrenal CD is difficult. Method: We report four cases of CD in the adrenal gland confirmed by pathology and review the characteristics of this rare disease, highlighting the necessity of diagnostic evaluation and follow-up of the patients. Results: All of the patients sought medical advice because of adrenal incidentalomas. No significant abnormalities were presented in the biochemistry or endocrine systems. The imaging suggested a moderate-to-large mass with uneven moderate contrast enhancement of the adrenal region, similar to a pheochromocytoma. All cases were misdiagnosed as pheochromocytomas before operation and finally confirmed by histopathology. Three cases were pathologically diagnosed as hyaline vascular CD, and one case was diagnosed as plasma cell CD. All the patients are alive without recurrence after a median follow-up of 8 years. Conclusion: The adrenal CD should be considered after excluding pheochromocytoma and malignancy in the adrenal region. The long-term prognosis of patients with complete resection of the mass is excellent.